2001
DOI: 10.1063/1.1375002
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of Mg-doped Ba0.96Ca0.04Ti0.84Zr0.16O3 thin films fabricated by metalorganic decomposition method

Abstract: Mg-doped Ba0.96Ca0.04Ti0.84Zr0.16O3 (BCTZ) thin films have been proposed as a promising material for microelectronic device applications based on high dielectric materials. Perovskite polycrystalline Mg-doped BCTZ thin films were fabricated on a Pt/Ti/SiO2/Si substrate by metalorganic decomposition method. Dielectric properties were improved after a Pt/Mg-doped BCTZ thin film/Pt capacitor was post-annealed at 700 °C in O2 atmosphere for 30 min. A high dielectric constant of 460 at 1 MHz, a low dissipation fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…These results are in good agreement with the ones obtained by Pontes et al [15]. On the other hand, the results obtained by Yi et al [16] are quite different, since the oxygen post-annealing treatments in that study were done at high temperatures (700 jC), which led to the filling of oxygen vacancies, consequently enhancing the dielectric properties of the thin films.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These results are in good agreement with the ones obtained by Pontes et al [15]. On the other hand, the results obtained by Yi et al [16] are quite different, since the oxygen post-annealing treatments in that study were done at high temperatures (700 jC), which led to the filling of oxygen vacancies, consequently enhancing the dielectric properties of the thin films.…”
Section: Resultssupporting
confidence: 88%
“…They observed that these properties are considerably sensitive to the post-annealing treatment. Moreover, Yi et al [16] observed better dielectric properties in Mg-doped (Ba,Ca)(Ti,Zr)O 3 thin films postannealed in oxidizing atmospheres.…”
Section: Introductionmentioning
confidence: 97%
“…11 Not much work has been performed on the dielectric properties and tunabilities of BCZT ceramics. The fabrication of BCZT thin films by metal-organic decomposition 12 and radio frequency magnetron sputtering, 13 and their dielectric properties and tunability have been reported recently. There are a few papers reporting on the diffuse phase-transition characteristics and effects of grain size and dc electric field on the dielectric properties of ͑Ba, Ca͒ ϫ͑Zr y Ti 1−y ͒O 3 ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…6. Comparing the results between the post-annealed sample and the as-deposited sample, we can see the dielectric relaxation is greatly improved by the post-annealing due to the fact that the postannealing process in oxygen ambient enhances the dielectric properties by reduction of oxygen vacancy concentration [15,21]. Furthermore, for the same reason, the post-annealed sample possesses much more excellent dielectric tunability, i.e., 40.6% at an electric field intensity of 278 kV/cm (not shown here).…”
Section: Resultsmentioning
confidence: 93%